2020
DOI: 10.1016/j.jid.2020.03.951
|View full text |Cite
|
Sign up to set email alerts
|

Skin Microbiome in Cutaneous T-Cell Lymphoma by 16S and Whole-Genome Shotgun Sequencing

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Indeed, CTCL exhibits an impaired skin barrier and deficient expression of several AMPs leads to increased susceptibility for skin infections and bacterial toxins may play a major role in driving disease progression [55,59,67,68]. Since microbial colonization is not consistent between CTCL patients, as shown in an early study by Axelrod et al [14] and extended by two investigations utilizing microbiomics [20,21], differential microbial colonization may account for transcriptional heterogeneity.…”
Section: Single Cell Transcriptome Signatures Suggest Microbial Influ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, CTCL exhibits an impaired skin barrier and deficient expression of several AMPs leads to increased susceptibility for skin infections and bacterial toxins may play a major role in driving disease progression [55,59,67,68]. Since microbial colonization is not consistent between CTCL patients, as shown in an early study by Axelrod et al [14] and extended by two investigations utilizing microbiomics [20,21], differential microbial colonization may account for transcriptional heterogeneity.…”
Section: Single Cell Transcriptome Signatures Suggest Microbial Influ...mentioning
confidence: 99%
“…Salava et al used 16S and WMS to investigate the microbiome on early stage CTCL lesions while using non-lesional skin of the same patients as an internal control [21]. WMS data delivered higher resolution in the genus of propionibacteria as compared to 16s sequencing and subsequent analysis is therefore based on WMS.…”
Section: Microbiome On Ctcl Lesionsmentioning
confidence: 99%
See 1 more Smart Citation
“… 108 A recent study based on 16S rRNA and whole-genome shotgun sequencing revealed a relative reduction in a suite of opportunistic pathogens in active mycosis fungoides skin lesions compared with that in contralateral healthy-looking skin. 109 Moreover, increased early oral exposure to the microbiome conveys a protective role for young adult HL, 110 and maladjusted microbiota of the oral cavity and conjunctiva have been reported in cases with paediatric ALL and conjunctival MALT lymphoma, respectively. 111 , 112 While the mechanistic role is undefined, these data highlight that the commensal microbiome outside the GIT may play a role in malignant lymphocyte transformation and consequently may serve as a therapeutic target.…”
Section: Associations Of Microorganisms Beyond the Git With Lymphomamentioning
confidence: 99%
“…Furthermore, the human microbiota has tremendous potential to impact multiple human physiological functions including immune homeostasis (Belkaid and Hand, 2014). Dysbiosis, alterations of the microbial communities that lead to detrimental effects on the host, has been proposed to contribute to the genesis of several diseases of the lymphohematopoietic system, including Hodgkin lymphoma, gastric mucosa-associated lymphoid tissue (MALT) lymphoma, acute lymphoblastic leukemia and cutaneous T cell lymphoma (Cozen et al, 2013;Raderer et al, 2016;Rajagopala et al, 2016;Salava et al, 2020). Of them, Helicobacter pylori infection with gastric MALT lymphoma constitutes a paradigm for microbiota-driven malignancy (Raderer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%